Pengaruh Gaya Kepemimpinan, Motivasi, Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Huawei Tech Investment - Jaenudin, Jaenudin; Firlana Whydia Putra; fanesya Desilfa; Iskandar Ahmaddien (Jurnal Dinamika Ekonomi & Bisnis, 2020)
This study aims to determine the effect of leadership style, motivation, and work discipline on performance at PT. Huawei Tech Investment. There are negative factors that reduce the performance of employees of PT. Huawei Tech Investment, including decreased employee desire to achieve work performance, lack of timeliness in completing work so that they do not comply with regulations, influence that comes from their environment, coworkers who also decline in enthusiasm and there are no examples that should be used as a reference in achieving work performance. well. This research method uses a quantitative approach method. Data collection techniques by distributing questionnaires directly to employees of PT. PT. Huawei Tech Investment uses google form with a sample of 50 people. Using the descriptive analysis method and SEM (Structural Equetion Modeling) research method with PLS (Partial Least Square) analysis with the help of PLS 2.0 software. Based on the results of the analysis of factors that significantly influence employee performance are motivation and work discipline because it is proven in the hypothesis test with the t-statistic greater than the t-table, while the leadership style does not have a significant effect on employee performance.